2002
DOI: 10.1016/s1074-5521(02)00245-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the π-π Stacking Interactions between the Aminoglycoside Antibiotic Kinase APH(3′)-IIIa and Its Nucleotide Ligands

Abstract: A key contact in the active site of an aminoglycoside phosphotransferase enzyme (APH(3')-IIIa) is a pi-pi stacking interaction between Tyr42 and the adenine ring of bound nucleotides. We investigated the prevalence of similar Tyr-adenine contacts and found that many different protein systems employ Tyr residues in the recognition of the adenine ring. The geometry of these stacking interactions suggests that electrostatics play a role in the attraction between these aromatic systems. Kinetic and calorimetric ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 72 publications
1
48
0
Order By: Relevance
“…However, the electrostatic potential of heterocyclic adenine and guanine nucleobases of DNA/RNA differ markedly from that of homocyclic conjugated systems such as benzene. Calculations of the electrostatic potential map of adenine illustrates that the negative charge is concentrated on N1, N3, and N7, whereas C8 and N9 have significant positive potential (12). Similar studies on the electrostatic potential of tryptophan suggest a relatively greater negative potential on the six-member ring of the indole side chain than on the five-member heterocycle (13).…”
Section: Resultsmentioning
confidence: 70%
“…However, the electrostatic potential of heterocyclic adenine and guanine nucleobases of DNA/RNA differ markedly from that of homocyclic conjugated systems such as benzene. Calculations of the electrostatic potential map of adenine illustrates that the negative charge is concentrated on N1, N3, and N7, whereas C8 and N9 have significant positive potential (12). Similar studies on the electrostatic potential of tryptophan suggest a relatively greater negative potential on the six-member ring of the indole side chain than on the five-member heterocycle (13).…”
Section: Resultsmentioning
confidence: 70%
“…These data suggest that the proposed hydrophobic cavity is the common binding pocket for agonists and antagonists in TodS. The aromatic side chain of F79 in TodS appears to play a central role in the recognition of a broad series of ligands, and we propose effector recognition to be dominated by pi-pi stacking interactions of effectors and protein residues, a common feature in the molecular recognition of aromatic ligands by proteins (27,28).…”
Section: Discussionmentioning
confidence: 76%
“…K395 stabilizes the complex from the other side via a cation-interaction ( fi g. 4 ). Both interactions contribute with low binding energies of probably -2 to -5 kcal/mol [Boehr et al, 2002;Gallivan and Dougherty, 2000], which corresponds to the low observed K D value of 1.4 m M . The nucleotidebinding mode of KdpBN thus differs from other ATPbinding domains.…”
Section: The Nucleotide-binding Modementioning
confidence: 87%